A complex hierarchical quorum-sensing circuitry modulates phenazine gene expression in Pseudomonas aeruginosa - Abd El-Aziz, Norhan Khairy; Abd El-Hamid, Marwa Ibrahim; El-Naenaeey, El-sayed Youssef (The Journal of Infection in Developing Countries, 2018)
Introduction: Pseudomonas aeruginosa (P. aeruginosa) modulates the expression of a myriad of virulence factors via two complicated hierarchical quorum-sensing (QS) cascade. This study shed light on the interrelation between P. aeruginosa QS systems and pyocyanin production. Methodology: Transcription analysis of lasR, rhlR, rhlI and phz genes using quantitative real time-reverse transcriptase PCR (qRT–PCR) assay, followed by sequencing of the autoinducer synthase (lasI gene) were applied for 15 P. aeruginosa strains recovered from diverse animal clinical sources. Results: Expression studies revealed that most P. aeruginosa strains demonstrated statistically significant differences (p < 0.05) with a very wide range of transcript levels of QS and phz genes in comparison to P. aeruginosa ATCC 27853. We have identified significant positive correlations (r ≥ 0.3) between the expressions of QS and phz genes in eleven analyzed strains, whereas pyocyanin production positively correlated with the expression of lasR only in three strains (r ≥ 0.6). We further found that there was a negative correlation between the transcript levels of QS and phz genes in one bacterial strain. Analysis of lasI sequences showed point mutations explaining the alterations in pyocyanin expression. The deficiencies of lasI, lasR and rhlI with rhlR-dependent expression of phz in one strain were also recorded. Conclusions: These results provided new insights to the pivotal role of QS signal molecules on pyocyanin production presenting the las system as the dominant regulator.